Pengaruh Perilaku Inovatif dan Motivasi Kerja Terhadap Kinerja Guru Penggerak SMP di Kabupaten Magetan - Didin Anshori; Anang Kistyanto; Dewie Tri Wijayati Wardoyo (LP. Ma'arif Janggan Magetan, 2024)
Research on the Influence of Positive Behavior and Work Motivation on the Performance of Driving Teachers in Magetan Regency was made with the aim of analyzing how innovative behavior and Work Motivation have a positive and significant effect on Teacher Performance in Magetan Regency. This research is quantitative research with a causality survey method of influence between independent variables and dependent variables which can be used to simultaneously describe the linear relationship between observed variables (indicators) and variables that cannot be measured directly (latent variables) (Prihandini & Sunaryo: 2011 ) and data processing was processed using the SPSS.27 program and data collection techniques through questionnaires with respondents of 72 Middle School Level Teachers in Magetan Regency.In this research, it was found that innovative behavior and work motivation had a positive and significant effect on the performance of middle school driving teachers in Magetan Regency and for future research it is recommended to find other variables outside this research that could influence the performance of driving teachers.Keywords: Innovative Behavior, Work Motivation, Driving Teacher Performance